The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-97998-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant system response, mineral element uptake and safe utilization of Polygonatum sibiricum in cadmium-contaminated soil

Abstract: Chinese herbal medicine is widely cultivated in Southwest China, where the soil cadmium (Cd) contamination of farmland is more serious than that in China as a whole. In this study, Polygonatum sibiricum was exposed to Cd at concentrations of e−1, e0, e2, and e4 mg/kg for 30, 60, and 90 days, and the physiological stress responses, Cd and mineral element uptake, antioxidant enzyme activities, and content changes of pharmaceutical ingredients (polysaccharides) were analyzed to decipher the feasibility of safe ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…As long as the pollution does not exceed the norm of the reaction of a particular type, an increase in the content of these metabolites is observed, and with a stronger technogenic pollution, a decrease is observed. It has recently been suggested that it is possible to achieve an increase in yield and the content of pharmacologically valuable substances in some types of plants when grown on soil contaminated with HM (subject to mandatory control of environmental cleanliness) [15,61,62]. This is very promising for plants whose medicinal raw materials are fruit, seeds, or flowers, i.e., parts characterized by the least accumulation of toxicants.…”
Section: Nonmonotonic Dependences Of the Content Of Phenolic Compound...mentioning
confidence: 99%
See 1 more Smart Citation
“…As long as the pollution does not exceed the norm of the reaction of a particular type, an increase in the content of these metabolites is observed, and with a stronger technogenic pollution, a decrease is observed. It has recently been suggested that it is possible to achieve an increase in yield and the content of pharmacologically valuable substances in some types of plants when grown on soil contaminated with HM (subject to mandatory control of environmental cleanliness) [15,61,62]. This is very promising for plants whose medicinal raw materials are fruit, seeds, or flowers, i.e., parts characterized by the least accumulation of toxicants.…”
Section: Nonmonotonic Dependences Of the Content Of Phenolic Compound...mentioning
confidence: 99%
“…This is very promising for plants whose medicinal raw materials are fruit, seeds, or flowers, i.e., parts characterized by the least accumulation of toxicants. The possibility of growing Polygonatum sibiricum plants in soil contaminated with cadmium was shown, which makes it possible to obtain tubers with a high content of active substances, polysaccharides [61]. Similarly, an increase in the quantity and quality of the essential oil of Cymbopogon citratus (D.C.) Stapf.…”
Section: Nonmonotonic Dependences Of the Content Of Phenolic Compound...mentioning
confidence: 99%
“…The Huangjing, known as 'immortal food', has the effect of tonifying qi and blood, invigorate the spleen and moisten the lung, as well as bene ting the kidney in theory of traditional Chinese medicine [2]. These three kinds of medicinal plants of Polygonatum family are widely distributed and rich in resources in China, of which the P. sibiricum mostly grows in the northeast and north China, the P. cyrtonema Hua is primarily concentrated in Hunan, Zhejiang, and Anhui of the mountainous areas [3][4][5]. Huangjing has the characteristics of medicine and food homology.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on P. sibiricum have shown that the antioxidant system (including superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD)) is the main resistance mechanism against Cd stress [ 20 ]. However, P. sibiricum is a low Cd accumulator and therefore can be safely planted in Cd-contaminated soils [ 20 , 21 ]. However, such information is limited for P. cyrtonema.…”
Section: Introductionmentioning
confidence: 99%